Degradation of iridium oxides via oxygen evolution from the lattice: correlating atomic scale structure with reaction mechanisms. Issue 12 (28th October 2019) - Kasian, Olga; Geiger, Simon; Li, Tong; Grote, Jan-Philipp; Schweinar, Kevin; Zhang, Siyuan; Scheu, Christina; Raabe, Dierk; Cherevko, Serhiy; Gault, Baptiste; Mayrhofer, Karl J. J.
Abstract : Combination of atom probe tomography, isotope-labelling and online electrochemical mass spectrometry provides direct correlation of atomic scale structure of Ir oxide catalysts with the mechanism of oxygen formation from the lattice atoms. Abstract : Understanding the fundamentals of iridium degradation during the oxygen evolution reaction is of importance for the development of efficient and durable water electrolysis systems. The degradation mechanism is complex and it is under intense discussion whether the oxygen molecule can be directly released from the oxide lattice. Here, we define the extent of lattice oxygen participation in the oxygen evolution and associated degradation of rutile and hydrous iridium oxide catalysts, and correlate this mechanism with the atomic-scale structures of the catalytic surfaces. We combine isotope labelling with atom probe tomography, online electrochemical and inductively coupled plasma mass spectrometry. Our data reveal that, unlike rutile IrO2, Ir hydrous oxide contains –Ir III OOH species which directly contribute to the oxygen evolution from the lattice. This oxygen evolution mechanism results in faster degradation and dissolution of Ir. In addition, near surface bulk regions of hydrous oxide are involved in the oxygen catalysis and dissolution, while only the topmost atomic layers of rutile IrO2 participate in both reactions. Overall our data provide a contribution to the fundamental understanding of the exceptional stability of Ir-oxides towards the oxygen evolution reaction. The proposed approach to a quantitative assessment of the degree of lattice oxygen participation in the oxygen evolution reaction can be further applied to other oxide catalyst systems.